Social support and managing schizophrenia in Tanzania: Perspectives from treatment-engaged individuals and relative caregivers - Praxeda Swai; Monica Desjardins; Anna Minja; Jennifer Headley; Paul Lawala; Liness Ndelwa; Carina Maboja; Joseph Temu; Ellen Lukens; Sylvia Kaaya; Joy Noel Baumgartner (Elsevier, 2024)
Background: In lower-resource settings like Tanzania, people living with schizophrenia (PWS) rely on their families for much of their social support, thus leading family members to become their main caregivers. How PWS and their families understand and implement social support can profoundly impact recovery pathways. This study examines how PWS and caregivers of PWS in Tanzania describe receiving and giving social support. We describe, from the perspectives of treatment engaged PWS and unmatched caregivers, different types of social support experienced and provided and examine any differences in the types and expectations of social support expressed by PWS versus caregivers. Methods: A total of 39 semi-structured in-depth interviews were conducted with PWS (n = 19) and caregivers (n = 20) recruited from outpatient psychiatric clinics in tertiary-level hospitals in Tanzania across two geographic regions. Thematic content analyses were based on four dimensions of social support (instrumental, emotional, informational, and appraisal). Results: Results revealed four themes: 1) Financial and basic needs support from families is common yet critical for daily living (instrumental support); 2) There were mixed experiences regarding provision and receipt of love and acceptance with desires and calls for more encouragement and moral support (emotional support); 3) Caregivers try to provide knowledge, guidance, and reminders related to illness management for PWS but acknowledge their own gaps in understanding recovery promotion and effective caregiving (informational & appraisal supports), 4) A cross-cutting issue was calls for more social support from the wider community. Conclusion: Social support is a multi-dimensional construct recognized by PWS and caregivers as critical for illness management, yet gaps remain, often due to lack of knowledge of how to bolster social support. Given the heavy reliance on families for social support in lower-resource contexts, psychiatric services can intervene with clinic-based psychoeducation for PWS and their families to improve quality of life and functioning.